2018
DOI: 10.3389/fneur.2018.00137
|View full text |Cite
|
Sign up to set email alerts
|

Combined Treatment With Dichloroacetic Acid and Pyruvate Reduces Hippocampal Neuronal Death After Transient Cerebral Ischemia

Abstract: Transient cerebral ischemia (TCI) occurs when blood flow to the brain is ceased or dramatically reduced. TCI causes energy depletion and oxidative stress, which leads to neuronal death and cognitive impairment. Dichloroacetic acid (DCA) acts as an inhibitor of pyruvate dehydrogenase kinase (PDK). Additionally, DCA is known to increase mitochondrial pyruvate uptake and promotes glucose oxidation during glycolysis, thus enhancing pyruvate dehydrogenase (PDH) activity. In this study, we investigated whether the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 59 publications
0
21
0
Order By: Relevance
“…Previous studies have shown that DCA plays an essential role in vascular protection and in promoting revascularization of blood vessels (Deuse et al, 2014; Hong et al, 2018) and improves vascular calcification in patients with atherosclerosis (Yang Y. et al, 2018). DCA might also have therapeutic effects in the context of vascular-related diseases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that DCA plays an essential role in vascular protection and in promoting revascularization of blood vessels (Deuse et al, 2014; Hong et al, 2018) and improves vascular calcification in patients with atherosclerosis (Yang Y. et al, 2018). DCA might also have therapeutic effects in the context of vascular-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies had found that DCA acts as a potential vasoprotective agent by inhibiting PDK2 and reducing coronary endarterium proliferation (Deuse et al, 2014). Further, DCA promotes brain regeneration after cerebral ischemia (Hong et al, 2018), which indicates that DCA might play an important role in VD.…”
Section: Introductionmentioning
confidence: 99%
“…Under the ischemic condition, disruption of brain homeostasis is disturbed and cell death mechanisms are initiated. This cerebral injury leads to an alteration in ionic balance within the intra-extracellular space [ 6 ], reactive oxygen species (ROS) production [ 7 ], microglia [ 8 ] and astrocyte [ 9 ] activation, zinc accumulation [ 10 ], and neuronal cell degeneration [ 11 , 12 , 13 ] in the brain. Blockage of blood flow to the brain by ischemic insult causes tissue infarction, dysfunction of ionic balance, and intracellular calcium overload [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In general, previous studies showed that PDK inhibits PDH via phosphorylating PDH after brain injuries, such as ischemia or epilepsy, thereby restricting the pyruvate oxidation (PO) pathway available to brain cells. As a result, under this pathological condition, the citric acid cycle cannot proceed and the production of ATP decreases, leading to cell death [26,27].…”
Section: Introductionmentioning
confidence: 99%